Posturografia com estímulos de realidade virtual nas diferentes disfunções vestibulares - Yamamoto, Marcelo Eiji Inoue [UNIFESP] (2012)
PURPOSE: To assess body balance and to quantify possible alterations over the static posturography of the Balance Rehabilitation Unit (BRU TM) in patients with vestibular dysfunction. METHODS: Retrospective study, with files of 100 patients with topographic diagnosis of peripheral or central vestibular dysfunction and 100 healthy individuals that composed the control group, of both genders, with ages varying between 7 and 86 years. For the posturography, the Balance Rehabilitation Unit (BRU TM), of Medicaa® was used. The following parameters were analyzed: stability limits, elliptical area, and speed of oscillation in ten sensory conditions. RESULTS: Mean values ​​of the stability limit, the elliptical area and the speed of oscillation in the experimental group was significant when compared to the control group in all conditions. The mean parameters of the female experimental group were significant when compared to the control group in all conditions. Patients with central vestibular dysfunction obtained higher values than patients with peripheral vestibular dysfunction in the variables elliptical area and speed of oscillation, however with lower value of the area of the stability limit. CONCLUSION: Posturography with virtual reality stimuli was an effective assessment method for detecting alterations related to the variables stability limits, elliptical area, and speed of oscillation, since the control group performed better, both between groups and between genders. Among the vestibular dysfunctions, individuals with peripheral condition performed better than those with central vestibular dysfunction in all the variables analyzed on posturography.